Pro Kontra Pengaturan Pencegahan dan Penanganan Kekerasan Seksual di Perguruan Tinggi: Tinjauan Perspektif Hukum Islam - Muhammad Akmal Rizki Rivaldi; Anisa Fernanda; Baidhowi Baidhowi (Mutawasith: Jurnal Hukum Islam, 2021)
The government through the Ministry of Education, Culture,Research, and Technology issued Ministerial Regulation No. 30 of 2010 to deal with and preventsexual violence. However, the regulation has many pros and cons in the community. One of themis the polemic of the use of the phrase "without the consent of the victim" which is considered thelegalization of adultery, immoral intercourse, and free sex which has the potential to damage thenation's character and morals and is contrary to social and religious norms, especially the Islamicreligion. This article aims to review these regulations which contain elements of legalizingadultery, immoral acts, and free sex in the perspective of Islamic law. By using a descriptiveanalytical approach as a result of the normative legal method, it can be concluded that Islamiclaw with its source of Islamic law, namely the Qur'an, forbids just approaching adultery,committing adultery, let alone legalizing it.